Hubungan Penggunaan Diapers Dengan Kemampuan Toilet Training Pada Anak Toddler Di Desa Jrahi Pati - Uyun, Khumrotul, Siti Arifah, S.Kp., M.Ke, Dian Nur W, S.Kep., Ns., M.Kep (2016)
Toddler age is the age of 1-3 years or toddlers, which is a period of growth and development of children is very fast, so if encounter obstacles it will have an impact on the growth and development of the next child. One task of this child is potty training toddler training. Children, who use diapers, will typically experience a delay toilet training. The delay caused by the child feels that it is not necessary to go to the toilet because when using diapers still feel comfortable even after doing BAK. This study aims to determine the relationship of the use of diapers to toilet training in children's ability toddler in the village Jrahi. This research is descriptive correlative with cross sectional approach. Sample study was 49 aged 18-36 months in the village Jrahi Gunungwungkal Subdistrict Pati with purposive sampling technique. Collecting data using questionnaires were analyzed using Spearman Rank test. The results using Spearman Rank test robs values obtained 0.570 with p-value 0.0001 thus concluded there is a relationship diapers use with ability toilet training. Concclusions were: (1) the use of diapers mostly in the category of routine (57%), (2) the ability of toilet training largely in the category enough (55%), and (3) there is a significant relationship between the use of diapers to the ability of toilet training in children toddler age 18-36 months in the village Jrahi Gunungwungkal Subdistrict Pati. Keywords: the use of diapers, toilet training, children toddler